2020
DOI: 10.1371/journal.ppat.1009001
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent secreted bacterial effectors reveal active intravacuolar proliferation of Listeria monocytogenes in epithelial cells

Abstract: Real-time imaging of bacterial virulence factor dynamics is hampered by the limited number of fluorescent tools suitable for tagging secreted effectors. Here, we demonstrated that the fluorogenic reporter FAST could be used to tag secreted proteins, and we implemented it to monitor infection dynamics in epithelial cells exposed to the human pathogen Listeria monocytogenes (Lm). By tracking individual FAST-labelled vacuoles after Lm internalisation into cells, we unveiled the heterogeneity of residence time ins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 49 publications
(71 reference statements)
3
26
0
Order By: Relevance
“…SLAPs are nonacidic and non-degradative phagosomes generated in an autophagy dependent manner, which maintain a sub-population of intracellular L. monocytogenes producing low amounts of LLO. More recently, live fluorescent microscopy of Listeria infection of epithelial cells revealed that a subset of bacteria remains within long-term vacuoles, where they can proliferate as quickly as cytosolic ones [ 238 ]. Cytoplasmic L. monocytogenes has also been shown to switch from an active motile lifestyle to a stage of persistence within vacuoles in epithelial and trophoblast cells during several days of infection.…”
Section: Listeria Crossing the Intestinal Barriermentioning
confidence: 99%
“…SLAPs are nonacidic and non-degradative phagosomes generated in an autophagy dependent manner, which maintain a sub-population of intracellular L. monocytogenes producing low amounts of LLO. More recently, live fluorescent microscopy of Listeria infection of epithelial cells revealed that a subset of bacteria remains within long-term vacuoles, where they can proliferate as quickly as cytosolic ones [ 238 ]. Cytoplasmic L. monocytogenes has also been shown to switch from an active motile lifestyle to a stage of persistence within vacuoles in epithelial and trophoblast cells during several days of infection.…”
Section: Listeria Crossing the Intestinal Barriermentioning
confidence: 99%
“…Prototypical FAST is a small protein tag (14 kDa) with reduced genetic footprint, which was originally designed to fluoresce instantaneously upon non-covalent binding of fluorogenic 4-hydroxybenzylidene rhodanine (HBR) derivatives that are inherently non-fluorescent unless bound to FAST 13 . Recent studies showed that FAST enabled (i) to circumvent some limitations of conventional fluorescent proteins—allowing for instance the imaging of proteins in strict anaerobic organisms 14 , 15 or the visualization of protein secretion by bacteria in real time 16 , 17 —and (ii) to bioengineer functional biosensors for monitoring intracellular analytes 18 , and observing protein–protein interactions with high spatial and temporal resolution 19 . Capable of binding various membrane permeant and membrane-impermeant HBR derivatives 13 , 20 , 21 , prototypical FAST exhibited great potential for engineering a multifunctional fluorescent chemogenetic reporter with tunable color through chromophore modulation.…”
Section: Introductionmentioning
confidence: 99%
“…As these vacuoles shared features of SLAPs [ 18 ], but supported extensive intravacuolar L . monocytogenes replication as reported for eSLAPs [ 22 ], we named them replication-permissive SLAPs (rSLAPs). At the time of high intra-vacuolar L .…”
Section: Resultsmentioning
confidence: 99%
“…In epithelial cells, epithelial SLAP-like vacuoles (eSLAPs) were recently reported. eSLAPs share some features with SLAPs such as decoration with LC3, LAMP1, as well as neutral pH [ 22 ]. However, eSLAPs support rapid intravacuolar L .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation